Implementation of Counseling Techniques: Art Therapy Techniques to Explore the Problems of Introverted Students Who Experience Academic Procrastination - Devianti, Rika; Nurhafiza, Nurhafiza; Pane, Riem Malini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aim is to describe the implementation of art therapy technique in individual conseling to explore the problems of introvert students. The research method was qualitative method with case study approach. the research subject was 1 student at x grade students in Tembilahan. The technique in collecting data used interview, observation and documentation. the research data analyzed triangulation data. Based on the result, it shws that the art therapy technique can explore the problems of introvert students. the students can tell their story, and have confidence in solving their problems after following conseling by art therapy technique. art therapy technique in conseling can apply flexsibley as a tool to open the conversation, or combine the media of art therapy technique with the profesional abilty of conseling teacher as communication media in therapeutic relathionship. Art therapy technique can help the students to express their thought and feelings througt drawing, painting, or coloring the observed object based on feeling and mood. art thechnique can help the students who cannot express their problems verbally and this technique can help the students to express their problems implicitly through a series of arts.